Diagnóstico de la producción apícola y meliponícola en los cantones de Macará, Paltas, y Gonzanamá de la provincia de Loja - Agila Yanangómez, Renan Gustavo (2015)
This research was conducted in the cantons of Macara, Paltas; and Gonzanamá province of Loja; in order to make a diagnosis of beekeeping and meliponícola production, which aims to: Determine production systems; prepare a proposal based on the management and production; and thus disseminate the project results to representatives of associations of beekeepers in a canton. Seven variables of study were established: Operating systems, management, nutrition, health, production, marketing; and organization survey was applied to 103 farmers engaged in beekeeping and meliponícola activity. According to the type of bee species, the results indicate that 67% of farmers manage Apis mellifera, while 33% managed meliponas. The operating system is the predominant family (70.42%), with a population of hives per apiary of 1-12 units. With respect to management hive, the 19.15% of producers taking into account the existence of Queen, 31.43% the size of the population; and 47.72% consider the reservation of honey in the colony. The 80.12% of producers do not provide supplementary food to bees, only provided 19,88%. Referring to Health on 62.94% of producers say the non-presence of bee diseases and meliponícolas; 12.12% while the attacks of varroa manifest; and ants; the production of honey per hive is 15.33 liters, and three drawer meliponas; 52.85% same as the producers intended for home consumption and for sale 47.15%. The price of a liter of honey from Apis mellifera is $ 11.33, russet (17); Catiana (15). Beekeepers Association "San Antonio" in the field of Laguar is the collection center for storing and processing honey .